2010
DOI: 10.1007/s00520-010-0985-8
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the control of nausea and vomiting with chemotherapy of low or minimal emetic potential

Abstract: More data are needed on the emetic potential and the outcome of antiemetic treatment with agents likely to fall into the low or minimal emetic potential category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…This anxiety could lead to the inclusion of prophylactic antiemetic drugs in future chemotherapeutic regimens and potentially contribute to the overuse of antiemetic drugs. 20 We also found similar levels of use in a demographic of patients who are generally better at controlling their vomiting 33 relative to the overall patient population, which indicates that the use of antiemetic drugs for chemotherapy with low and minimal emetic risk is predetermined, regardless of the individual patient's risk. Recent studies have suggested the importance of identifying a patient's individual risk for CINV.…”
Section: Discussionsupporting
confidence: 59%
“…This anxiety could lead to the inclusion of prophylactic antiemetic drugs in future chemotherapeutic regimens and potentially contribute to the overuse of antiemetic drugs. 20 We also found similar levels of use in a demographic of patients who are generally better at controlling their vomiting 33 relative to the overall patient population, which indicates that the use of antiemetic drugs for chemotherapy with low and minimal emetic risk is predetermined, regardless of the individual patient's risk. Recent studies have suggested the importance of identifying a patient's individual risk for CINV.…”
Section: Discussionsupporting
confidence: 59%
“…Possibly, the effects are centrally mediated through inhibition of both prostaglandin synthesis and endogenous opioid release [17]. Glucocorticoids may be equal to or better than other drugs such as ondansetron, or metoclopramide in preventing nausea and vomiting associated with chemotherapy and post procedural sedation [18,19]. Ondansetron and dexamethasone have similar efficacy when administered for antiemetic prophylaxis in adults [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reported incidence of grade 3/4 vomiting was 8% in the Le Cesne trial [10]. Grade 3 vomiting is defined as experiencing more than 6 episodes of vomiting in the last 24 h. In addition, in most reported trials a preventive antiemetic regimen was already applied and makes a correct risk classification even more complicated, as the emetic risk classification depends on the risk of emesis without the use of antiemetics [27]. For a better overview, the reported rates of nausea and vomiting are depicted for the major trials in Table 3.…”
Section: Emetic Risk Classification Of Trabectedinmentioning
confidence: 97%